Global Contextualities and Alberta Muslim Women’s Health - Waugh, Earle H. (Religious studies and theology, 2015)
Muslim women living in Canada and the United States of America are subject to many influences and the global nature of Islam is one of them. While it is evident that research on so large and diverse a category as Muslim women’s health could flounder on a number of issues, it is nevertheless crucial that the cohort be examined, even if cursorily, so that we may appreciate the many subtle influences impacting the cohort. Furthermore, regardless of the difficulties in segregating these women from the social matrices within which they live around the world, the fact is they personally insist that the common label "Muslim" has validity. Hence no sampling of Muslim women’s lives in Alberta can be complete without highlighting how their health is registered through a "Muslim" cultural prism. That in turn indicates that global dimensions help shape their well-being. This essay aims to do a preliminary survey of the field with the hope that others will do a more comprehensive analysis.